2017
DOI: 10.1038/srep42297
|View full text |Cite
|
Sign up to set email alerts
|

Ran-dependent TPX2 activation promotes acentrosomal microtubule nucleation in neurons

Abstract: The microtubule (MT) cytoskeleton is essential for the formation of morphologically appropriate neurons. The existence of the acentrosomal MT organizing center in neurons has been proposed but its identity remained elusive. Here we provide evidence showing that TPX2 is an important component of this acentrosomal MT organizing center. First, neurite elongation is compromised in TPX2-depleted neurons. In addition, TPX2 localizes to the centrosome and along the neurite shaft bound to MTs. Depleting TPX2 decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…Given that γ-tubulin, augmin, and TPX2 interact with each other and that MT nucleation from the sides of existing MTs requires all three proteins in Xenopus egg extract (Petry et al, 2013), it is tempting to speculate that RanGTP promotes ncMT nucleation by releasing TPX2 from the inhibitory importin heterodimers which in turn activating the γ-tubulin-augmin-TPX2 complex at the neurite tip. In support of this hypothesis, TPX2 and augmin complex subunits have been observed to localize along neurites (Chen et al, 2017;Cunha-Ferreira et al, 2018). In addition, both importin-α and importin-β molecules have been observed to present throughout the cytoplasm in cultured neurons (Chen et al, 2017;Hanz et al, 2003).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Given that γ-tubulin, augmin, and TPX2 interact with each other and that MT nucleation from the sides of existing MTs requires all three proteins in Xenopus egg extract (Petry et al, 2013), it is tempting to speculate that RanGTP promotes ncMT nucleation by releasing TPX2 from the inhibitory importin heterodimers which in turn activating the γ-tubulin-augmin-TPX2 complex at the neurite tip. In support of this hypothesis, TPX2 and augmin complex subunits have been observed to localize along neurites (Chen et al, 2017;Cunha-Ferreira et al, 2018). In addition, both importin-α and importin-β molecules have been observed to present throughout the cytoplasm in cultured neurons (Chen et al, 2017;Hanz et al, 2003).…”
Section: Discussionmentioning
confidence: 72%
“…It has been reported that RanGTP is enriched at the soma and the neurite tip (Chen et al, 2017). To confirm this localization, an antibody which specifically targets the C-terminal tail of Ran GTPase that is only exposed in the GTP-bound state (Richards et al, 1995) was used for immunofluorescence staining to examine 2 days in vitro (2DIV) dissociated hippocampal neurons.…”
Section: Ran Gtpase Affects Microtubule Formation At the Neurite Tipmentioning
confidence: 99%
See 3 more Smart Citations